Testing the Systemic Model of Social Disorganization Theory in South Korean Neighborhoods: A Latent Class Growth Analysis Approach to Specifying Pathways to Homicide - Cho, Sujung (Homicide studies, 2021)
This study examines the relationship between structural characteristics and homicide trajectories in South Korean neighborhoods utilizing the systemic model of social disorganization theory as an analytical lens. Group-based trajectory modeling of Korean homicide data across 229 municipal-level sub-national regions between 2008 and 2013 yielded three groups: high-decrease, moderate, and low-stable. The odds of belonging to the high and moderate groups compared to the low-stable group were significantly increased for communities with a higher-level divorce rate and residential instability rate. Social control was significant in the high-decrease group compared to the low-stable group, but had no mediating effect on this relationship.